2021
DOI: 10.1088/2053-1591/abde59
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and abrasive wear properties of high-vanadium-chromium wear resistant alloy

Abstract: To enhance the wear resistance of high chromium cast iron (HCCI, Cr26), a new wear resistant alloy with high vanadium and chromium contents (HCCI-V, 15Cr5V4MoSiMn) was designed and prepared by sand mold casting. The microstructure and the phase composition were analyzed by SEM, EDS and XRD, and the abrasive wear property was tested compared with HCCI. Results show that the new wear resistant alloy is characterized by multi-scale and multi-type carbides distributed in a metal matrix composed of martensite and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Therefore, the search and development of wear materials with even better properties have been pursued [28][29][30][31][32]. Preliminary research has shown that the lifespan of high-vanadium steel rollers is five times longer than that of high-chromium cast iron rollers [33,34]. Meanwhile, the lifespans of crusher hammers and jaws, made from high-speed steels intended for use in the crushing industry, are three times and 10 times longer than those of highchromium cast iron and high-manganese steel, respectively [35,36].…”
Section: Effect Of Carbon Contentmentioning
confidence: 99%
“…Therefore, the search and development of wear materials with even better properties have been pursued [28][29][30][31][32]. Preliminary research has shown that the lifespan of high-vanadium steel rollers is five times longer than that of high-chromium cast iron rollers [33,34]. Meanwhile, the lifespans of crusher hammers and jaws, made from high-speed steels intended for use in the crushing industry, are three times and 10 times longer than those of highchromium cast iron and high-manganese steel, respectively [35,36].…”
Section: Effect Of Carbon Contentmentioning
confidence: 99%
“…For the excellent properties, wear-resistant steel with V and Cr is often used in long-life production conditions of abrasive wear [1]. Traditional design method is time-consuming and costly.…”
Section: Introductionmentioning
confidence: 99%